Direct ingestion, trophic transfer, and physiological effects of microplastics in the early life stages of Centropristis striata, a commercially and recreationally valuable fishery species. (15th September 2021) - Stienbarger, Cheyenne D.; Joseph, Jincy; Athey, Samantha N.; Monteleone, Bonnie; Andrady, Anthony L.; Watanabe, Wade O.; Seaton, Pamela; Taylor, Alison R.; Brander, Susanne M.
Abstract: Microplastics are ubiquitous in marine and estuarine ecosystems, and thus there is increasing concern regarding exposure and potential effects in commercial species. To address this knowledge gap, we investigated the effects of microplastics on larval and early juvenile life stages of the Black Sea Bass ( Centropristis striata ), a North American fishery. Larvae (13–14 days post hatch, dph) were exposed to 1.0 × 10 4, 1.0 × 10 5, and 1.0 × 10 6 particles L −1 of low-density polyethylene (LDPE) microspheres (10–20 μm) directly in seawater and via trophic transfer from microzooplankton prey (tintinnid ciliates, Favella spp.). We also compared the ingestion of virgin and chemically-treated microspheres incubated with either phenanthrene, a polycyclic aromatic hydrocarbon, or 2, 4-di-tert-butylphenol (2, 4-DTBP), a plastic additive. Larval fish did not discriminate between virgin or chemically-treated microspheres. However, larvae did ingest higher numbers of microspheres through ingestion of microzooplankton prey than directly from the seawater. Early juveniles (50–60 dph) were directly exposed to the virgin and chemically-treated LDPE microspheres, as well as virgin LDPE microfibers for 96 h to determine physiological effects (i.e., oxygen consumption and immune response). There was a significant positive relationship between oxygen consumption and increasing microfiber concentration, as well as a significant negative relationship between immune response and increasing virgin microsphere concentration. This first assessment of microplastic pollution effects in the early life stages of a commercial finfish species demonstrates that trophic transfer from microzooplankton can be a significant route of microplastic exposure to larval stages of C. striata, and that multi-day exposure to some microplastics in early juveniles can result in physiological stress. Graphical abstract: Image 1 Highlights: Larval sea bass ingest more microplastics from ciliate prey than from the water. Exposure to fibers causes increased oxygen consumption in juvenile sea bass. Exposure to virgin microspheres decreased immune response in juvenile sea bass. Presence of phenanthrene or di-tert butyl phenol did not influence ingestion. Presence of associated chemicals did not affect respiration or immune response.